Headache in Behçet's disease: case reports and literature review - M. Govoni; F. Trotta; R. La Corte; A. Lo Monaco; J.G. Capone; C. Monaldini; S. Volpinari (PAGEPress Publications, 2011)
Objective: To evaluate the prevalence of headache and its different patterns in patients with Behçet's disease (BD) with and without neurological involvement and to investigate clinical correlations. Methods: Patients fulfilling the International Study Group criteria for Behçet disease (ISGc) were studied. Patients were invited to fill a "headache questionnaire", which consisted of two sections: the first one included demographic and anamnestic data, family history for both headache and BD, disease duration and clinical manifestations of BD; the second section included items about headache, investigated accordingly to International Headache Society diagnostic criteria (IHS, 2004). Clinical history and current comorbidities-medications were collected. Each patient underwent a neurological examination to assess neurological involvement (Neuro-BD) and, if necessary, instrumental investigations. One hundred-fifty healthy subjects matched for age and gender were used as control group for comparison. Results: Of the 55 patients diagnosed as BD (ISG criteria) 41 patients adhered and were enrolled into the study. Headache occurred in 29 of BD patients (70,7%) and in 13 of Neuro-BD patients (92,8%). Migraine without aura did prove the most frequent type of headache in BD patients (with and without neurological involvement) and there were no differences in the frequency of the different pattern of headache between BD patients and controls. Conclusions: Headache is a frequent manifestation in BD and primary headache like migraine emerged as the most frequent type of headache. A careful search for headache should be included in the diagnostic work-up of BD since this manifestation may be related to the underlying disease.